2006 Florida Citrus Pest Management Guide: Huanglongbing (Citrus Greening) - Ronald H. Brlansky; Kuang-Ren Chung; Michael E. Rogers (EDIS, 2019)
Huanglongbing (HLB), commonly called citrus greening disease, is caused by the bacterium, Candidatus Liberibacter spp. The name huanglongbing means “yellow dragon” which describes the symptom of a bright yellow shoot that commonly occurs on a sector of infected trees. HLB is a serious disease of citrus because it affects all citrus cultivars and causes rapid decline of trees. This document is PP-225, one of a series of the Plant Pathology Department, UF/IFAS Extension. Original publication date November 2005.